Association of Obesity, Diabetes, and Risk of Tuberculosis: Two Population-Based Cohorts. (26th September 2017) - Lin, Hsien-Ho; Wu, Chieh-Yin; Wang, Chih-Hui; Fu, Han; Lönnroth, Knut; Chang, Yi-Cheng; Huang, Yen-Tsung
Abstract : In 2 large Taiwanese cohorts, obesity had a harmful effect on tuberculosis mediated through diabetes but had a strong protective effect not mediated through diabetes. Individuals who were simultaneously obese and diabetic had a 70% reduction in tuberculosis risk. Abstract: Background: Mounting data have revealed that body mass index (BMI) is inversely associated with risk of active tuberculosis. The inverse association presents a "paradox" with regard to diabetes, because obesity is a major determinant of diabetes, and diabetes is a well-known risk factor for tuberculosis. Methods: We conducted 2 population-based cohort studies involving 167392 participants. The main exposure was BMI and diabetes ascertained at baseline. Occurrence of incident tuberculosis was ascertained from Taiwan's National Tuberculosis Registry. We conducted a causal mediation analysis and a joint effects analysis to characterize the relationship between BMI, diabetes, and tuberculosis. Results: During a median of >7 years of follow-up, 491 individuals developed incident tuberculosis. Compared with normal-weight individuals, obese individuals (>30 kg/m 2 ) had a 67% (95% confidence interval [CI], −3% to −90%) and 64% (31%–81%) reduction in tuberculosis hazard in the 2 cohorts. In the causal mediation analysis, obesity had a harmful effect on tuberculosis mediated through diabetes (0.8% and 2.7% increased odds in the 2 cohorts, respectively) but had a strongly protective effect not mediated through diabetes (72% and 67% decreased odds, respectively). Individuals who were simultaneously obese and diabetic had a lower but statistically insignificant risk of tuberculosis (adjusted hazard ratio, 0.30; 95% CI, .08–1.22) compared with nondiabetic normal-weight individuals. Conclusions: Our analyses revealed that the relationship between obesity, diabetes, and risk of tuberculosis was complex and nonlinear. Better understanding of the interplay between host metabolism and tuberculosis immunology may lead to novel therapeutic or preventive strategies.